Herzog's Kinski and Bergman's Ullmann: The Auteur and the Actor in Autobiographical Films (Communication & Society, 2001)
The idea of the cinematic author implies that a single artistic vision creates a film, and that this vision is a highly personal one. In fact, a film made by an auteur is supposed to reflect in some way the persona of the director/author and can be understood as autobiographical, though the definition of autobiography must be redefined in order to accommodate film. The collaborative nature of film, for example, seems to undermine the very essence of autobiography. This paper examines the work of two highly personal filmmakers, Ingmar Bergman and Werner Herzog, looking in particular at the highly dynamic relationships forged between these men and their actors. What might these relationships tell us about the nature of cinematic autobiography?